2000
DOI: 10.1562/0031-8655(2000)072<0340:cfsaai>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Common Fluorescent Sunlamps are an Inappropriate Substitute for Sunlight¶

Abstract: Fluorescent sunlamps are commonly employed as convenient sources in photobiology experiments. The ability of Kodacel to filter photobiologically irrelevant UVC wavelengths has been described. Yet there still remains a major unaddressed issue--the over representation of UVB in the output. The shortest terrestrial solar wavelengths reaching the surface are approximately 295 nm with the 295-320 nm range comprising approximately 4% of the solar UV irradiance. In Kodacel-filtered sunlamps, 47% of the UV output fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The wavelengths of UVR most effective in causing adverse effects on the skin of hairless mice, including sunburn, photoimmunosuppression, and skin carcinogenesis, are UVB [49-51]. Thus, most photobiology studies that employ hairless mice are carried out using UVR sources that emit UVB or mixed UVB and UVA wavelengths [52]. …”
Section: Photobiology Of Hairless Micementioning
confidence: 99%
See 1 more Smart Citation
“…The wavelengths of UVR most effective in causing adverse effects on the skin of hairless mice, including sunburn, photoimmunosuppression, and skin carcinogenesis, are UVB [49-51]. Thus, most photobiology studies that employ hairless mice are carried out using UVR sources that emit UVB or mixed UVB and UVA wavelengths [52]. …”
Section: Photobiology Of Hairless Micementioning
confidence: 99%
“…UVR directly induces cyclobutane pyrimidine dimers and (6-4) photoproducts in DNA [50,52]. Exposure to UVB also indirectly induces oxidative DNA damage, in part through the ROS generated by infiltrating inflammatory cells and activated keratinocytes.…”
Section: Photobiology Of Hairless Micementioning
confidence: 99%
“…This may pose little problem if the object is to irradiate small areas of skin but for studies where large numbers of experimental animals or plants are to be irradiated, the limited irradiation field is a real problem. Because of this attention has turned to fluorescent lamps as sources of simulated UV [9]. One way to evaluate candidate lamps and decide which is the most appropriate approximation to sunlight is to calculate the percentage relative cumulative erythemal effectiveness (%RCEE) for a number of wavebands and to compare these values with the %RCEE values of a ''standard sun'' [10].…”
Section: Fluorescent Lampsmentioning
confidence: 99%
“…It has been demonstrated that vehicles can dramatically affect the absorption and deposition of glycolic acid into the skin [6]. Further, the choice of light source has been shown to significantly affect biological responses to UV radiation [43,44]. Therefore, the use of a vehicle (cream) that closely mimics those used in consumer products and an artificial light source that closely duplicates solar radiation (sunlight) are critical factors in designing these types of studies.…”
Section: Discussionmentioning
confidence: 99%